Professor Fisher and the quantity theory: A significant encounter - David Laidler (The University of Western Ontario, Department of Economics, 2011)
Irving Fisher's encounter with the Quantity theory of Money began in the 1890s, during the debate about bimetallism, and reached its high point in 1911 with the publication of The Purchasing Power of Money. His most important refinement of the theory, derived from his recognition of bank deposits as means of exchange, was to treat their out of equilibrium recursive interaction with inflation as integral to it. This treatment underlay both his 1920s work on the business cycle as a dance of the dollar and his advocacy of subjecting monetary policy to a legislated price stability rule, initially to be based on his compensated dollar scheme. Fisher's failure to recognize the onset of the Great Depression even as it was happening was directly related to his faith in the quantity theory's seeming implication that price level stability in and of itself guaranteed the continuation of prosperity, while his subsequent work on the debt deflation theory of great depressions initially failed to repair the damage that this failure did to his reputation, and to that of the quantity theory. In the 1930s Fisher nevertheless remained an active supporter of various schemes to reflate and then stabilize the price level. His subsequent influence on the quantity theory based Monetarist counter-revolution that began in the 1950s lay, directly, in its deployment of his analysis of expected inflation on nominal interest rates, and, indirectly, in its espousal of the case for subjecting monetary policy to a legislated rule.n.
Keywords: B1; B2; B3; E3; E4; E5; 330; Quantity Theory; Price Level; Inflation; Deflation; Business Cycle; Depression; Money; Interest; Fisher Effect; Geldtheorie; Quantitätstheorie